Growth of Al2O3 thin film by oxidation of resistively evaporated Al on top of SnO2, and electrical properties of the heterojunction SnO2/Al2O3 - Maciel, Jorge L. B. [UNESP]; Floriano, Emerson A. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Ravaro, Leandro P. [UNESP] (Springer, 2011)
Aiming for the investigation of insulating properties of aluminum oxide (Al2O3) layers, as well as the combination of this oxide with tin dioxide (SnO2) for application in transparent field effect transistors, Al thin films are deposited by resistive evaporation on top of SnO2 thin films deposited by sol-gel dip-coating process. The oxidation of Al films to Al2O3 are carried out by thermal annealing at 500 A degrees C in room conditions or oxygen atmosphere. X-ray diffraction data indicate that tetragonal Al2O3 is indeed obtained. A simple device and electric circuit is proposed to measure the insulating properties of aluminum oxide and the transport properties of SnO2 as well. Results indicate a fair insulation when four layers or Al2O3 are grown on the tin dioxide film, concomitant with thermal annealing between each layer. The current magnitude through the insulating layer is only 0.2% of the current through the semiconductor film, even though the conductivity of the SnO2 alone is not very high (the average resistivity is 2 Omega cm), because no doping is used. The presented results are a good indication that this combination may be useful for transparent devices.